Note—A Multiple-Item Inventory Model with a Job Completion Criterion - Graves, Stephen C. (Management Science, 1982)
Most office equipment is maintained by service organizations consisting of teams of service representatives. An important problem for the service organizations is the determination of the spare parts inventory to be carried by each service representative. This note presents a model for finding the spare parts kit that has the minimum inventory investment for a specified job completion criterion. The model is shown to be equivalent to a binary knapsack problem. The model is contrasted with the model developed by Smith, Chambers and Shlifer for a similar problem.